What Do We Know About Young Adult Cardiac Patients' Experience? A Systematic Review - Journiac, Jonathan; Vioulac, Christel; Jacob, Anne; Escarnot, Coline; Untas, Aurélie (Frontiers in Psychology, 2020)
Background: studies interested in patients coping with a cardiac illness usually focus on children, teenagers, and adults above the age of 55. Apart from the field of congenital heart diseases, there is a general lack of literature regarding young adult cardiac patients (18-55 years old), who seem to cope with psychosocial issues. Therefore the objective of this paper was to gather all the research carried out concerning the psychological experiences of young adult cardiac patients. Methods and results: a comprehensive, systematic review was conducted on quantitative, qualitative, and mixed method studies in PsycINFO, PubMed, ScienceDirect, and Cochrane Library databases. Out of the 10747 articles found, 32 were included. While we aimed to include many cardiac diseases, coronary patients dominated the data. Five main themes emerged: emotional states (depression, anxiety, emotional distress, stress), quality of life (health-related quality of life, physical functioning, sexuality), adjusting to the medical environment (coping with the disease, health behaviour change, financial barriers, interactions with medical professionals), social life (social support, work), and identity (parenthood, new challenges, new meanings). Results highlighted that levels of depression, anxiety, stress, and quality of life were sometimes worse than in the general population and than in older and younger patients coping with a cardiac illness. Social isolation, identity changes, work, and parenthood were the specific challenges this population had to face. Furthermore, young adult cardiac patients showed worse health behaviour profiles than the general population and felt that they lacked information from professionals, especially regarding sexuality. Compared to men, women had worse psychosocial outcomes, especially regarding depression, stress, emotional distress, and quality of life. Conclusions: young adult cardiac patients are to be considered with their own identity and challenges. They may be in need of specific interventions, some dedicated to women, and better communication is necessary with their families and professional caregivers, so as to improve patient mental health, quality of life, coping skills, and adherence.